ANALYSIS OF ADVANCED SEARCH ENGINE MECHANISMS - MENGATOVA XURSHIDA TOSHMUXAMATOVNA; ESONTURDIYEV MAMATKOBIL NURMAMATOVICH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article presents an analysis of the mechanism of work of advanced search engines, which are currently developing and have a wide range of capabilities. Have been studied technologies for extracting text data from text files (txt), HTML pages (htm, html), Adobe Acrobat files (pdf), MS Word and MS Excel files (doc, docx, xls, xlsx), multimedia files (mp3, avi, mpeg, etc.) and executable files (exe) in search engines. The indexing processes were analyzed, as well as the stages of data search and sorting of results. The results of the analysis can be used to develop general functional requirements for a database of electronic documents when creating an advanced search system.